Assessment and comparison of periodontal status and its impact on oral health-related quality of life among urban and rural adults of Uttar Pradesh: A cross-sectional study - Sasmita Dalai; Pradeep Tangade; Vikas Singh; Ankita Jain; Surbhi Priyadarshi; Jagriti Yadav (Wolters Kluwer Medknow Publications, 2022)
Context: Periodontal diseases negatively influence people's oral health-related quality of life (OHRQoL) and despite advancements; still disparity exists among urban and rural dwellers. OHRQoL helps in a better understanding of subjective perception ensuring a better treatment plan that fits the patient's needs and concerns. Aims and Objectives: (1) To record the periodontal status of urban and rural populations of Moradabad using WHO pro forma 2013. (2) To assess and compare the OHRQoL using the oral health impact profile-14 (OHIP-14). Subjects and Methods: A cross-sectional study was conducted among the rural (350) and urban (350) population of Moradabad aged 35-44 years, chosen from the outpatient department of Teerthanker Mahaveer Dental College and Hospital. The WHO oral health assessment form for adults (2013) was used to assess the periodontal status and OHIP-14 was used for assessing OHRQoL. Statistical Analysis Used: SPSS version 19.0 was used for statistical analysis. Chi-square, Student's t-test, and multiple logistic regression analysis were employed for statistical analysis. Results: The prevalence of loss of attachment (LOA) (93.20%), presence of pocket (76.0%), and bleeding on probing (BOP) (74.0%) was significantly higher among the rural population. The mean OHIP scores were significantly higher for the rural population as compared to urban counterparts. Among the study population, OHIP 14 was significantly (P ≤ 0.05) associated with age, gender, socioeconomic status, location, and periodontal parameters (LOA, Pocket, and BOP). Conclusions: The study shows that there is a significant association between periodontal status and OHRQoL. Rural individuals had a greater impact on OHRQoL than their urban counterpart. Strategies should be planned and implemented to minimize the disparity.